Synthesis of N1-Substituted 1,2,3,6-Tetrahydropyrimidin- 2-ones via an Unexpected Reaction of Thiazolo[3,2-a]-pyrimidine Derivatives and Nitrile Oxide - Li, Xiaofang; Yi, Pinggui; Yu, Xianyong (Chinese journal of chemistry, 2010)
A new class of N1‐substituted 1,2,3,6‐tetrahydropyrimidin‐2‐ones was prepared in moderate yields by the reaction of nitrile oxide with thiazolo[3,2‐a]pyrimidine derivatives via a domino 1,3‐dipolar cycloaddition/ring‐opening/ substitution process. The structures of the products were characterized thoroughly by IR, elemental analysis, MS, NMR together with X‐ray crystallographic analysis. A new class of N1‐substituted 1,2,3,6‐tetrahydropyrimidin‐2‐ones were prepared in moderate yields by the reaction of nitrile oxide with thiazolo[3,2‐a]pyrimidine derivatives via a domino 1,3‐dipolar cycloaddition/ring‐opening/substitution process. The structures of the products were characterized thoroughly by IR, elemental analysis, MS and NMR together with X‐ray crystallographic analysis.